FINANCIAL PERFORMANCE OF ENGINEERING COMPANIES IN AN EMERGING ECONOMY: BEFORE AND AFTER COVID-19 - Md Shakib Hossen; Shoishab Roy; Mofijul Hoq Masum (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2023)
The COVID-19 pandemic had a significant impact on numerous companies in emerging economies, including the engineering sector, due to factors such as lockdown restrictions and disruptions in the supply chain. Moreover, many companies within the engineering sector witnessed a decline in their financial performance as a result of the pandemic. This study is conducted to assess the influence of COVID-19 on the financial performance of the engineering sector in emerging country - Bangladesh. The study considers the secondary data from the listed companies in Dhaka Stock Exchange, focusing on engineering companies. This study utilized a quantitative research methodology employing a thematic approach. To evaluate financial performance, changes in net profit, changes in revenue growth and three relative performance ratios - liquidity ratio, profitability ratio and solvency ratio are used to compare the corporate performance before and after the COVID-19 pandemic in Bangladesh. It is found that the financial performances in the listed companies in Bangladesh are not facing as much obstacle as it is observed in developed economy. This result implies that the impact of covid-19 is sharply visible in the economy but it is not as much risky as the developed economy. This result will help the corporate people in the developing economy to adopt necessary initiatives to cope up the upcoming natural issues.